The knowledge of pharmacists about cosmetics in pharmacies of Tehran, Iran - Golbarg Ghiasi; Farshad Hashemian; Abbas Kebriaeezadeh; Shaghayegh Ghiasi (Tehran University of Medical Sciences, 2017)
Background: Considering that the cosmetics today are not have used only for luxury purposes and have effective medicinal components, pharmacists require knowing about the components and ingredients of such products with a scientific level on different usages. As mentioned above, the main objective of this study is investigating the knowledge of pharmacists employed in the pharmacies of Tehran about cosmetics. Methods: This study has been conducted by descriptive method using surveys. For completing the surveys, referring to the pharmacies, in personal, and delivering the forms to pharmacists, they were asked to complete it in the same time and they returned it to the surveyor. Results: According to results, it can be seen that 57% of pharmacists generally answered correctly, i.e., the information of almost 43% of pharmacists for sunscreen cares seems not to be enough. Furthermore, the awareness of pharmacists about depilatories and their physicochemical properties and ingredients was weak (21.5%). Conclusion: It was considered as the only significant relation between age of pharmacists and their knowledge such that by increase in their age, their knowledge to two products, sunscreen care, and depilatory was decreased. On the other side, in Iran, the role of pharmacists has not been defined in this field-necessity of providing cosmetics information.